Biphenyl 2,3-Dioxygenase in Pseudomonas alcaliphila JAB1 Is Both Induced by Phenolics and Monoterpenes and Involved in Their Transformation - Zubrova, Andrea; Michalikova, Klara; Semerad, Jaroslav; Strejcek, Michal; Cajthaml, Tomas; Suman, Jachym; Uhlik, Ondrej (Frontiers in Microbiology, 2021)
The involvement of bacterial aromatic ring-hydroxylating dioxygenases (ARHDs) in the degradation of aromatic pollutants, such as polychlorinated biphenyls (PCBs), has been well studied. However, there is considerable speculation as to the origin of this ability. One hypothesis is centred on a connection between the ability to degrade aromatic pollutants and the necessity of soil bacteria to cope with and/or utilize aromatic secondary plant metabolites (SPMs). To investigate this connection, we researched the involvement of biphenyl 2,3-dioxygenase (BPDO), an ARHD essential for the degradation of PCBs, in the metabolism of SPMs in the soil bacterium Pseudomonas alcaliphila JAB1, a versatile degrader of PCBs. We demonstrated the ability of the strain JAB1 to transform a variety of SPMs, namely the flavonoids apigenin, naringenin, fisetin, quercetin, morin, and catechin, caffeic acid, trans-cinnamic acid, and the monoterpene (R)-carvone. Of those, the transformation of flavone, flavanone, and (S)-limonene was conditioned by the activity of JAB1-borne BPDO and thus was researched in more detail, and we found evidence for the limonene monooxygenase activity of the BPDO. Furthermore, the bphA gene in the strain JAB1 was demonstrated to be induced by a wide range of SPMs, with monoterpenes being the strongest inducers of the SPMs tested. Thus, our findings contribute to the growing body of evidence that ARHDs not only play a role in the catabolism of aromatic pollutants, but also of natural plant-derived aromatics, and this study supports the hypothesis that ARHDs participate in ecological processes mediated by SPMs.